Rasch Model Analysis on the Development of Digital Learning Model Using MOOCs in Practical Courses at University - Rosane Medriati; Eko Risdianto; Andik Purwanto; Kusen Kusen (STAI Hubbulwathan Duri, 2022)
This study aims to analyze the need for developing digital learning models using MOOCs in practical courses at universities using the Rasch Model. This research is part of Research and Development (R D) research but is only limited to the needs analysis stage. The population taken in this study were all undergraduate students at IAIN Curup. The sampling technique used is probability sampling with a total sample of 69 students from 17 study programs. The method used for data collection is a questionnaire. The instrument used in this research is a questionnaire on the need for developing a digital learning model using MOOCs in practical courses at IAIN Curup. The results showed that the quality of the student response questionnaires to the digital learning model using MOOCs in this practical course was very good. The results of the analysis of the respondents and the questionnaire items showed that the majority of respondents agreed with all the questionnaire items given, which means they agreed to do the model development digital learning using MOOCs in practical courses. These results can be used to support the implication of learning MOOCs in practical courses.